Anti-violence measures developed by ILO and WHO: Analysis of the prevalence of workplace violence and the effects of implementation in a general hospital in China - Yubing Hu; Yubing Hu; Qianqian Luo; Rui Li; Min Zhang; Yuming Wang; Peipei Su; Jing Sun; Ying Li; Yujie Liu; Na Chen; Yiming Huang (Frontiers Media S.A., 2022)
ObjectiveWorkplace violence (WPV) not only affects workers' physical and mental health but also increases turnover rates and social costs. There are no studies that have consistently followed the prevalence of WPV and the effectiveness of anti-violence measures in cross-sectional studies of the same hospital. The main aim of this study was to understand the prevalence of WPV among medical staff in a hospital in China and the effectiveness of implemented anti-violence measures.MethodsA cross-sectional survey, which was conducted by using a questionnaire developed by the International Labor Organization and the World Health Organization, was administered in a tertiary hospital in China in 2022 to investigate the occurrence of violence in the past year. Valid data were collected from 1,195 respondents via cell phone. WPV was compared between this survey and a baseline survey conducted at the same hospital in 2017 using the same questionnaire. The relationship between years and gender and occupation was explored using the Cochran-Armitage trend test. Descriptive statistics and chi-square tests were used to respond to the effects of the anti-violence interventions.ResultsAfter the implementation of anti-violence measures, the prevalence of WPV decreased from 48.47 in 2017 to 33.95% in 2021. The recognition of safety measures increased from 80.16 in 2017 to 87.70% in 2021(P < 0.001), improvement of the work environment increased from 56.57 in 2017 to 65.10% in 2021(P < 0.001), restricted of public access increased from 34.36 in 2017 to 55.60% in 2021(P < 0.001), the patient protocols increased from 37.42 in 2017 to 38.40% in 2021, patient screening increased from 32.11 in 2017 to 41.90% in 2021(P < 0.001), and strict restrictions on workplace cash activities from 29.65% in 2017 to 36.00% in 2021(P < 0.05). The percentage of health workers who felt that anti-violence measures were not at all helpful to their current work decreased from 2017 to 2021.ConclusionsThe prevalence of workplace violence has decreased, recognition of interventions has increased, and the proportion of interventions that are perceived by HWs as not helpful at all has decreased. This study demonstrates that the 12 anti-violence measures recommended by the International Labor Organization are applicable in China. Based on this, hospitals should focus on the improvement of the intervention effect of the following measures to further prevent violence.